2008
DOI: 10.1007/s00268-008-9848-6
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Monitoring of Adverse Events: Influence on the Quality of Care and the Incidence of Errors in General Surgery

Abstract: This is the first attempt to determine the prevalence of errors in surgery. Introducing systematic programs for recording adverse events can reduce error rates and promote a culture of patient safety in a General Surgery Department.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…This finding is in accordance with a previous study on complications and errors in surgical patients 27 . In another study of medical errors, technical failure was also one of the most frequent errors encountered 23 . In contrast, nurses are more likely to register medication errors, as illustrated in a study of adverse events, where more than 90 per cent of the events were recorded by nurses 28 ; the most common events (33 per cent) were medication-related, and surgical technical errors were hardly recorded.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This finding is in accordance with a previous study on complications and errors in surgical patients 27 . In another study of medical errors, technical failure was also one of the most frequent errors encountered 23 . In contrast, nurses are more likely to register medication errors, as illustrated in a study of adverse events, where more than 90 per cent of the events were recorded by nurses 28 ; the most common events (33 per cent) were medication-related, and surgical technical errors were hardly recorded.…”
Section: Discussionmentioning
confidence: 98%
“…The incidence of error was similar in the present investigation, ranging from 3·9 to 9·9 per cent depending on the surgical subspecialty under investigation. Studies addressing the incidence of errors in surgical patients have reported rates of 10·5 and 6·9 per cent respectively 6,23 . These figures are quite similar to the present results.…”
Section: Discussionmentioning
confidence: 99%
“…Many available error studies have reported only the incidence and pattern of medical errors and adverse events. Rebasa et al, 28 who performed a similar study, assessed only the change in the percentage of patients with errors over time, unlike the present study in which we assessed many variables, including the change in the number of errors per patient, proportion of patients with errors, severity of errors, preventability of errors, clinical impact of errors, complications of errors, and types of errors. The significant improvement noted in these error parameters in response to information from error reporting appears to make this study unique and versatile in providing information to health institutions yet to be convinced about the importance of error recording and reporting.…”
Section: Resultsmentioning
confidence: 69%
“…Abdominal wound dehiscence was reported was reported at a mean of 9 th postoperative day (6)(7)(8)(9)(10)(11)(12)(13)(14)(15). One patient reported with dehiscence after discharge from hospital after removal of sutures from a local hospital.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 In addition there is an increase in the cost of the care both in terms of increased hospital stay, nursing and manpower cost in managing the burst abdomen and its complication. [8][9][10][11][12] The disruption of the wound tends to occur a few days beforehand when the sutures opposing the deep layers tear through or even become untied. An incisional hernia starts as a symptomless partial disruption of the deep layers during the immediate or early postoperative period, even this passes unnoticed if the skin wound remains intact after the skin sutures have been removed.…”
Section: Introductionmentioning
confidence: 99%